Experiment on physical and mechanical properties of tomato seedling pot for automatic vegetable transplanter - Liang Xifeng; Cai Yangyang; Wang Yongwei (浙江大学学报. 农业与生命科学版, 2015)
China is the largest country of vegetable production in the world, and more than 60% vegetable varieties are planted by seedling transplanting, which mainly depends on manual work. However, there are some shortcomings in the traditional manual transplanting, such as high labor intensity, low productivity, poor quality and high cost. It is necessary to do some researches on the vegetable transplanters to adapt to the requirements of the mechanization of agricultural production. Currently, the domestic vegetable transplanters are mainly clip-chain transplanter, seedling guide tube transplanter, nacelle-type transplanter and flexible disc transplanter. The transplanters can meet the basic seedling transplanting requirements, but still stays in the semi-mechanization level. The research work of the vegetable transplanter is mainly focused on the design and optimization of the seedling picking and transplanting mechanism. However, automatic vegetable transplanter needs integrated knowledge and technology, the research on which should also combine the structural design with the physical and mechanical properties of vegetable seedling pot. Thus, it will be helpful for further optimal design of the key components of automatic vegetable transplanter, such as the picking seedling mechanism and the transplanting mechanism.Tomato seedlings with the age of 23 d were used as experiment objects. The physical and mechanical properties of the tomato seedling pot have been tested and analyzed, which were directly related to the transplanting machine design. Tablet compression of seedling pot has been done with a universal testing machine Instron 5543 and P100 flat probe. In the experiment, the regular pressure-deformation was analyzed and the clamping force characteristics of pot during seedling picking were determined. Pot puncture test using a universal testing machine Instron 5543 and P5 cylinder probe has been done to analyze the puncture characteristics of seedling pot during seedling picking. At the same time, to analyze the creep characteristics of seedling pot, creep test has been done using a universal testing machine Instron 5543 and P100 flat probe and combined with the describe of Burgers model. Then a scatter platform with 500 mm height was built and pots were scattered from the platform. The scattering rate of seedling was obtained and the scattering characteristics during transplanting were analyzed. Testing results show that the relationship between the capacity of resistance for compression and deformation was non-linear. The capacity of resistance for compression on yield point was 3.15 N when the deformation of the pot was 5.64 mm, so the picking seedling force should exceed the calculated yield point in the design of picking seedling machinery. In the puncturing process, the relationship between puncturing force and displacement was approximately linear at the displacement of 0 to 13.5 mm, and then it remained constant in the displacement range of 13.5 mm to 19.5 mm, while it increased significantly when the puncturing displacement was greater than 19.5 mm. Seedling pot creep property conformed to the creep law of Burgers model, and the average creep value was 0.398 9 mm in the condition of loading force of 5 N with 120 s retention time. In the scattering process, the tests showed the average scattering rate of seedling was 22.73%, and the seedling pots kept intact after falling, which met the requirements of mechanical planting.The research results on the physical and mechanical properties of vegetable seedling pot will provide important data for the design on the key components of automatic vegetable transplanters.